2011
DOI: 10.1001/archinternmed.2011.317
|View full text |Cite
|
Sign up to set email alerts
|

Safety-Net Providers After Health Care Reform

Abstract: Despite the significant reduction in uninsurance levels in Massachusetts that occurred with health care reform, the demand for care at safety-net facilities continues to rise. Most safety-net patients do not view these facilities as providers of last resort; rather, they prefer the types of care that are offered there. It will continue to be important to support safety-net providers, even after health care reform programs are established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
96
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 5 publications
2
96
1
Order By: Relevance
“…1517 Other studies attempted to isolate the effect of gaining insurance by assessing "natural policy experiments" in which individuals gained cover age because of a policy change, rather than a potentially confounding life event. 9,1822 For example, studies of Massachusetts' 2006 expansions found that patients who gained coverage used ambulatory care services at higher rates postcoverage. 9,1921 This body of quasiexperimental research is based on the assumption that the observed changes in outcomes are caused by a change in insur ance status and not due to unmeasured confounding variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1517 Other studies attempted to isolate the effect of gaining insurance by assessing "natural policy experiments" in which individuals gained cover age because of a policy change, rather than a potentially confounding life event. 9,1822 For example, studies of Massachusetts' 2006 expansions found that patients who gained coverage used ambulatory care services at higher rates postcoverage. 9,1921 This body of quasiexperimental research is based on the assumption that the observed changes in outcomes are caused by a change in insur ance status and not due to unmeasured confounding variables.…”
Section: Introductionmentioning
confidence: 99%
“…9,1921 This body of quasiexperimental research is based on the assumption that the observed changes in outcomes are caused by a change in insur ance status and not due to unmeasured confounding variables.…”
mentioning
confidence: 99%
“…6,11,12,15,71 Our findings come at a time when safety-net providers are caring for a sizeable portion of the newly insured population under the ACA, 72,73 while being underresourced and financially strained. 16,74,75 Notwithstanding the $11 billion the ACA committed for CHC expansion over 2010-2015, 34 the continuing financial challenges faced by safety-net providers may compromise access in low-income communities and undermine the quality of care by thwarting these institutions' ability to innovate in service delivery, improve quality, and participate in accountable care organizations.…”
Section: Discussionmentioning
confidence: 86%
“…4 Just such an increase in demand for community health centers was observed after the expansion of insurance coverage in Massachusetts. 11 As community health centers across the nation see more patients, the need for access to subspecialty care is likely to increase, too.…”
mentioning
confidence: 99%